2016
DOI: 10.1371/journal.pone.0159007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil Salinity on the Structure of the Bacterial Endophytic Community Identified from the Roots of Caliph Medic (Medicago truncatula)

Abstract: In addition to being a forage crop, Caliph medic (Medicago truncatula) is also a model legume plant and is used for research focusing on the molecular characterization of the interaction between rhizobia and plants. However, the endophytic microbiome in this plant is poorly defined. Endophytic bacteria play a role in supplying plants with the basic requirements necessary for growth and development. Moreover, these bacteria also play a role in the mechanism of salinity stress adaptation in plants. As a prelude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 76 publications
2
50
0
1
Order By: Relevance
“…It was demonstrated that plant growth promoting (PGP) abilities and biological nitrogen fixation, followed by the production of secondary metabolites and bioactive compounds, synthesis of fungicides and bactericides, and protection against environmental stresses are the most important benefits that are provided to plants by endophytes (Table 1). [39] Grasses (roots) Actinobacteria PGP abilities Agilent 2100 [40] Recently, Akinsanya et al [11] used NGS (mainly the Illumina method) for a metagenomic study of endophytes in Aloe vera and an assessment of their microbial diversity, whilst Yaish et al [8] conducted metagenomic studies of endophytes inhabiting Medicago truncatula roots. They found that Proteobacteria, Actinobacteria, Bacteroidetes were the dominant phyla of bacteria, and Firmicutes dominated in Aloe vera.…”
Section: Next Generation Sequencing Platforms As An Effective Tool Inmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that plant growth promoting (PGP) abilities and biological nitrogen fixation, followed by the production of secondary metabolites and bioactive compounds, synthesis of fungicides and bactericides, and protection against environmental stresses are the most important benefits that are provided to plants by endophytes (Table 1). [39] Grasses (roots) Actinobacteria PGP abilities Agilent 2100 [40] Recently, Akinsanya et al [11] used NGS (mainly the Illumina method) for a metagenomic study of endophytes in Aloe vera and an assessment of their microbial diversity, whilst Yaish et al [8] conducted metagenomic studies of endophytes inhabiting Medicago truncatula roots. They found that Proteobacteria, Actinobacteria, Bacteroidetes were the dominant phyla of bacteria, and Firmicutes dominated in Aloe vera.…”
Section: Next Generation Sequencing Platforms As An Effective Tool Inmentioning
confidence: 99%
“…Salt stress usually induces osmotic and ionic imbalance inside plant cells [8,92,93]. In unfavorable conditions, endophytes reduce stress in plants by synthesizing osmoprotectants, e.g., proline and/or trehalose, volatile organic molecules, and exopolysaccharides [8].…”
Section: Studies Of Improvement Of Ecological Adaptation Of the Host mentioning
confidence: 99%
See 1 more Smart Citation
“…All these mechanisms involve gene expression alterations [14,15], epigenetic changes [16][17][18], and community changes in the microbes associated with the plants [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Medicago truncatula when subjected to salinity stress [42], and also has been found in the endosphere of cannabis, potato and banana [43]- [45]. Other species enriched in both endospheres were P.…”
Section: Amplicon-based Taxonomic Profilingmentioning
confidence: 94%